Analisis Kebijakan Penganggaran pada Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Jambi - Zahara Zahara; Daryono Daryono; Zarmaili Zarmaili (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the budgeting process, factors that form the basis of budgeting and obstacles to the budget implementation and realization process at the Secretariat of the Regional People's Representative Council (DPRD) of Jambi Province. The analytical tool used is qualitative descriptive research. Based on the results of the study, it can be concluded that the budgeting process at the Secretariat of the Jambi Provincial DPRD follows the regional government budget cycle which consists of three main stages, namely budget preparation and determination, budget implementation, and APBD accountability reports. Budget preparation is carried out through coordination with the Executive Budget Team, then discussed with the DPRD before being ratified, while its implementation takes place after the APBD is approved, with accountability through semester and annual reports audited by BAWASDA and BPK to ensure transparency and accountability. Basic factors in budgeting include effectiveness, efficiency, and compliance with regulations. There are obstacles such as the incomplete discussion of the Draft Regional Regulation according to the Regional Legislation Program, changes in the number of Draft Regional Regulations that have an impact on activity planning, and low budget absorption due to external factors, such as changes in Central Government policies that complicate the preparation of the APBD. In addition, the lack of government assertiveness in enforcing policies and the suboptimal performance benchmarks complicate budget evaluation, so that improvements to the performance measurement system and better coordination between regional and central governments are needed.